Influence mechanism of force chain on jamming behavior in powder compaction based on 3D discrete element model - ZHANG Wei; XIAO Weijian; YUAN Chuanniu; ZHANG Ning; CHEN Rongxin (Fenmo yejin jishu, 2024)
To simulate the uniaxial powder compacting process, the 3D particle accumulation was generated by 3D discrete element method technology based on the experimental grading ratio. The evolution law and topological properties of the force chains were investigated during the powder compacting process, the jamming phenomenon was further studied using the velocity and coordination number of particles, and the correlation mechanism between the force chain and jamming behavior was discussed. The results show that, as the compression strength of the upper die gradually increases from 0 to 60 MPa, the number proportion of force chain particles rapidly increases to more than 40.0%, while the number proportion of high stress particles is stable above 12.5%. When the pressure exceeds 60 MPa, the force chains bend and form ring structure, causing the jamming phenomenon. As a result, the jammed point is set to 60 MPa. The jamming phenomenon also effects the powder densification. The axial velocity of the powder particles in the upper area is faster and the rangeability is larger than that of the powder particles in the lower area during the powder compaction process. However, when the compaction process is completed, the densification of the powder particles in the upper area is higher than that of the powder particles in the lower area.